Pre-service primary school teachers’ metacognitive awareness and beliefs about mathematical problem solving - Alper Yorulmaz; Hümeyra Uysal; Halil Çokçaliskan (Department of Mathematics Education, Universitas Muhammadiyah Surakarta, 2021)
Metacognitive awareness is a variable that is thought to affect beliefs in problem solving. When the literature is examined, it is seen that the studies mostly focus on metacognitive awareness and problem solving skills. Therefore, the aim is to determine pre-service primary school teachers’ metacognitive awareness and beliefs in mathematical problem solving. In this study, it is thought that it will contribute to the researches that will be carried out regarding the investigation of the relationship between metacognitive awareness and beliefs about problem solving and its implementation with pre-service primary school teachers. The study, designed as the correlational survey model, included a total of 284 pre-service primary school teachers attending a university in the Aegean Region of Turkey. The data were collected with the “Metacognitive Awareness Inventory” and the “Scale of Beliefs about Mathematical Problem Solving”. In the analysis, descriptive statistics, difference test, correlation and regression analyses were used. As a result, the pre-service primary school teachers’ metacognitive awareness was found to be high and their beliefs about mathematical problem solving were found to be medium. While metacognitive awareness was found to be not varying significantly by gender, beliefs about mathematical problem solving were found to be varying significantly by gender in favor of the male pre-service teachers. Moreover, a medium and significant correlation was found between metacognitive awareness and beliefs about mathematical problem solving. It was also found that metacognitive awareness explained 13% of the variance in the dependent variable of beliefs about mathematical problem solving.